How Wechat Has Changed the Face of Marketing in China - A. Yanes, Patricia; D. Berger, Paul (British Journal of Marketing Studies, 2017)
This paper discusses WeChat and considers how and why it has totally changed the way that marketing is done in China. WeChat is able to seamlessly join together a plethora of activities that combine several different platforms that are separate entities (e.g., Facebook, LinkedIn, PayPal, etc.) in the United States and the rest of the world. We first examine the censorship in China in the past and present, provide a short history of WeChat, and present the current status of WeChat with respect to several measures. We then delineate how WeChat is different from any other social-medial platform, and how it is able to positively infiltrate virtually all aspects of Chinese consumers’ lives. Lastly, we discuss how WeChat has already been emulated by other social-media platforms, and what to expect from WeChat in the future.